Transportation Fuel Use, Technology and Standards : The Role of Credibility and Expectations - Eskeland, Gunnar S. (World Bank, Washington, DC, 2012)
There is a debate among policy analysts about whether fuel taxes alone are the most effective policy to reduce fuel use by motorists, or whether to also use mandatory standards for fuel efficiency. A problem with a policy mandating fuel economy standards is the "rebound effect," whereby owners with more efficient vehicles increase vehicle usage. If an important part of negative externalities from transport are associated with vehicle kilometers (accidents, congestion, road wear) rather than fuel consumption, the rebound effect increases negative externalities. Taxes and standards should be mutually supportive because fuel taxes often meet political resistance. Over time, fuel efficiency standards can reduce political resistance to fuel taxes. Thus, by raising fuel efficiency standards now, politicians may be able to pursue higher fuel tax paths in the future. Another argument in support of fuel efficiency standards and similar policies is that standards to a greater extent than taxes can be announced in advance and still be credible and change the behavior of inventors, firms, and other agents in society. A further argument is that standards can be used with greater force and commitment through international coordination.